Clinical actions of midwives of neonatology units in a public hospital in Chile - Gálvez-Ortega, Pablo Francisco (2022)
Objective: To describe behaviors and clinical actions performed by midwives in the Neonatology Unit in Immediate Attention and Minimum Care of a hospital in Chile. Material and methods: Descriptive quantitative study applied to 21 midwives. A questionnaire validated by experts was carried out, which included professional actions. Results: The median age was 34 years. Of the Immediate Care actions, 19% perform aspiration of endotracheal secretions in patients with amniotic fluid with meconium. In Minimum Care, 71% do not install an arterial line. Many favor early contact for 30-60 minutes, not complying with the recommendation that encourages contact and delaying some procedures for 1 hour. Conclusion: The actions of the midwives in the chosen hospital center have been described and, based on them, determine behaviors that were not published in the current literature.